Intelligence and Security Informatics IEEE International Conference on Intelligence and Security Informatics, ISI 2006, San Diego, CA, USA, May 23-24, 2006. - Mehrotra, Sharad; Zeng, Daniel D.; Chen, Hsinchun (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2006)
In the past few years, intelligence and security informatics (ISI) research, which is concerned with the study of the development and use of advanced information te- nologies and systems for national and international security-related applications, has experienced tremendous growth and attracted substantial interest from academic - searchers in related fields as well as practitioners from both government agencies and industry. The ISI community is maturing, and a core set of research methodologies and technical approaches has emerged and is becoming the underpinning of ISI research. The first two meetings (ISI 2003 and ISI 2004) in the ISI symposium and conf- ence series were held in Tucson, Arizona. With sponsorship by the IEEE Intelligent Transportation Systems Society, ISI 2005 was held in Atlanta, Georgia. Building on the momentum of these ISI meetings, we held ISI 2006 in San Diego, California, in May 2006. In addition to the established and emerging ISI technical research topics, ISI 2006 included a track on terrorism informatics, which is a new stream of terrorism research leveraging the latest advances in social science methodologies, and infor- tion technologies and tools.